Effectiveness of parent involvementin providing nutrition and pmk towards body increase in bblr in the perinatology room of tarakan hospital, jakarta - dari, son; haryanto, Rohadi; Apriliawati, Anita (Jurnal Ilmiah Kesehatan, 2022)
Low born weight (LBW)  is a condition when a baby is born weighing less than 2500 grams, where this situation will have a negative impact on the development of the baby in the future. Proper nutrition is an important factor to support the growth and development of premature babies. Many factors influence nutritional status to make it better, including breastfeeding and Kangaroo Treatment (PMK). The purpose of this study was to determine the effectiveness of parental involvement in providing nutrition and PMK on increasing body weight in LBW. The research design used was quantitative with a quasi-experimental design with pre-test and post-test control group design approaches. The research sample consisted of 36 people consisting of 18 people in the intervention group and 18 people in the control group. This research was conducted in the Perinatology Room of the Tarakan Hospital, Jakarta. The results showed an overview of weight gain in the intervention group of 35.00 grams with p-value = 0,000 (p <0,000) and in the control group of 20.00 grams with p-value = 0.256 (p> 0,000). Parental involvement in nutrition and KMC has the largest difference than routine intervention in the room program, so the intervention of parental involvement in nutrition and KMC  has more influence on increasing body weight in LBW. Kata Kunci : Low Born Weight, Parental Involvement, Nutrition, Kangaroo Care Methods